Assessing The Physical Fitness Level of Students in Senior High Schools - Sarpong, Emmanuel Osei (International Journal for Innovation Education and Research, 2022)
The adolescent school going individuals face challenges as they go through the phases of development and academic work. Literature on physical fitness levels among such students in the second cycle institutions in Ghana is scarce, hence this study. The study assessed the physical fitness levels of 15-17-year-old students of St. Peters SHS in the Eastern Region of Ghana. Descriptive design with quantitative approach was adopted for the study. 60 participants were sampled for the study using purposive and simple random sampling techniques. The fitnessgram (made up of battery of tests) with attached checklists was used for data collection. The findings revealed that only one-third (33.3%) of the participants in St. Peters SHS had a cardiovascular endurance rating in the Healthy Fitness Zone (HFZ), with majority of them (66.7) in the “Needs Improvement” zone. Results further showed that majority of the participants had both muscular endurance and body mass composition ratings of (71.7% and 78.4%) with respect to Healthy Fitness Zone (HFZ) while only (28.3% and (21.6%) needed improvement. Results again affirm that, enjoyment and fun during physical education lessons (65%), attention given to injured students in a physical education class (93.3%), planned physical education classes (78.3%) and awareness of the importance of participation in physical education and sporting activities (71,6%) were relevant factors. Finally, results indicated that majority of the participants were in support of improving teaching and learning materials (TLMs) and facilities (86.7%) as well as making physical education a compulsory subject (71.7%). It was concluded that attention must be given to the cardiovascular health needs of the students in St. Peters SHS. Fun activities, injury prevention and treatment, appropriate planning of class sessions and provision of resources would promote and improve healthy active lifestyles amongst the student populace.